1999
DOI: 10.1590/s0102-35861999000500007
|View full text |Cite
|
Sign up to set email alerts
|

Medicina do sono

Abstract: No último encontro da American Thoracic Society, em abril de 1999, realizado em San Diego, CA, foram apresentados três trabalhos de autores brasileiros sobre medicina do sono, que passamos a comentar.O primeiro deles, feito em parceria entre a PUCRS (Porto Alegre) e a Universidade de Toronto (Canadá), estuda qualitativamente o óxido nítrico (NO) nasal e exalado, em pacientes portadores de síndrome da apnéia do sono obstrutiva (SASO). Os autores não encontram diferença estatisticamente significativa quando comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…antibodies in dogs reported in other studies in Brazil ranges from 2.66 to 85% in serological surveys (14)(15)(16)(17). In the present study, the observed occurrence was 20.08%, which corroborates previous studies.…”
supporting
confidence: 92%
“…antibodies in dogs reported in other studies in Brazil ranges from 2.66 to 85% in serological surveys (14)(15)(16)(17). In the present study, the observed occurrence was 20.08%, which corroborates previous studies.…”
supporting
confidence: 92%